Faktor-Faktor yang Mempengaruhi Persistensi Laba Perusahaan Makanan dan Minuman di BEI Tahun 2020-2023 - Lauren, Valencia; Susanti, Merry (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted to determine the effect of operating cash flow volatility, accruals, and debt level on earnings persistence in food and beverage sub-sector. This study used purposive sampling, with a sample size of 99 observations from 28 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for 4 years from 2020 to 2023. The data analysis method used was logistic regression analysis with the help of Eviews 12 software. The results of this study indicate that operating cash flow volatility and accruals have no significant effect on earnings persistence. While, debt level has a negative effect on earnings persistence